Increased accuracy of the phase characteristics of signals - Куц, Ю.В.; Лапіга, І.М.; Монченко, О.В. (Proceedings of National Aviation University (archive), 2006)
The mechanism of reception of a methodical error of measurements of the phase characteristic of signals is considered which arises owing to final time of processing, and way of its elimination with use of window processing. The example of realization of the offered technique is given.